2020
DOI: 10.1177/1087054720959707
|View full text |Cite
|
Sign up to set email alerts
|

Can Increased Recovery Rates from Coronavirus be explained by Prevalence of ADHD? An Analysis at the US Statewide Level

Abstract: Previous research demonstrates that ADHD is considered a risk factor for COVID-19. The current study attempts to investigate the relationships between infection, mortality and recovery rates from coronavirus and the prevalence of ADHD at the US statewide level. Based on information from 2011 regarding the prevalence of ADHD across the US by state, findings suggest that, while there are no correlations between ADHD and population size, infection and mortality rates from coronavirus, recovery rates (recovery-pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…ADHD has been found to be a risk factor for contracting COVID-19 [62] , particularly for females [63] , partially attributed to the non-adherence of government instructions such as social distancing or wearing masks [64] . However, in a US study, recovery rates (recovery-population ratio) have been found to rise with the prevalence of ADHD [65] suggesting that ADHD may present as a possible protective factor against severe COVID-19 symptoms.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…ADHD has been found to be a risk factor for contracting COVID-19 [62] , particularly for females [63] , partially attributed to the non-adherence of government instructions such as social distancing or wearing masks [64] . However, in a US study, recovery rates (recovery-population ratio) have been found to rise with the prevalence of ADHD [65] suggesting that ADHD may present as a possible protective factor against severe COVID-19 symptoms.…”
Section: Resultsmentioning
confidence: 92%
“…Some are reported to have higher transmission, infection and hospital rates [67] , [68] , such as B.1.617.2, otherwise known as the Delta variant. Although Arbel [65] identified higher recovery rates for people with ADHD in 2020, these findings may not be consistent with the emergence of the Delta variant or other future variants. At the present time, there is little published research into the short-term effects of the Delta variant for young people, adults and older adults and there has not been enough time to determine the long-term consequences of this variant for both ADHD and non-ADHD individuals.…”
Section: Discussionmentioning
confidence: 90%
“…Arbel et al performed an ecological study of the impact of ADHD prevalence on COVID-19 infection and prevalence and found impact only on recovery rates but not on infection. While interesting, the meaning and implications of their results seem to require further deliberations (Arbel et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they proposed that ADHD might provide an evolutionary advantage, as with the natural immunity to malaria brought by sickle-cell disease. This might explain our findings that ADHD could lead to higher odds of hospitalized COVID-19 rather than critically ill COVID-19 ( 30 ). However, more studies are needed before a definitive answer is reached.…”
Section: Discussionmentioning
confidence: 76%